Assessment of knowledge of HIV and AIDS among tribal college students: a cross-sectional study - Ghodke, Baliram; Mohite, Amit; Shinkar, Swapnil (International Journal Of Community Medicine And Public Health, 2020)
Background: AIDS mainly affects people aged 15-40 years. The co-infection of HIV/AIDS with other infectious diseases is an escalating public health problem. Public health intervention tools are effective only when knowledge needs are ably assessed. The objective of this study was to assess knowledge regarding HIV, routes of transmission, prevention and treatment in tribal students. Methods: Questionnaire was used to carry out this study in 120 tribal students enrolled in BA (bachelor of Arts) course in a college of tribal district of Maharashtra. Results: Out of 120 students, 104 students 86.67% completed the self-administered questionnaire. Out of 104 the 62.50% were males and 37.50% were females. 99.03% were aware of the word ‘HIV/AIDS’. 58.65% were aware of all possible routes of HIV transmission. Only 12.5% knew that unprotected anal sex carries high risk for HIV transmission.70.19% knew that HIV infection was not curable. 75% students said that weight loss was the major symptom of AIDS. 49.03% knew that tuberculosis was the principal opportunistic infection. 25% were aware of the ELISA test and 21.03% knew the location of treatment centre. The main sources of this information were television and the internet (72% and 71%). Conclusions: Tribal students have inadequate knowledge regarding routes of HIV transmission and its prevention. It is imperative to increase awareness by various channels of communications such as the mass media.